Daya Dukung Air untuk Daya Dukung Lingkungan di Kabupaten Semarang, Provinsi Jawa Tengah - Vitalia Irmawati; Sri Rahayu (Jurusan Perencanaan Wilayah dan Kota, 2020)
Water carrying capacity is the capability of water to meet needs by considering water availability. This research uses quantitative approach methods. While the formula used to calculate the air carrying capacity is the runoff coefficient method of Permen LH No.17 in 2009 by comparing the water availability and water needs. The study of water carrying capacity is done to know the carrying capacity of water in Semarang Regency. The results of this study showed that the water carrying capacity in Semarang Regency in general in 2018 has a deficit, with the value of water carrying capacity at 0.66. However, three out of nineteen subdistricts can still meet their water needs or water surpluses is the subdistricts of Banyubiru, Susukan and Sumowono with each of the value of water carrying capacity of 2.58, 1.09 and 1.04. Meanwhile, in 2028 showed a decrease in the value of water carrying capacity in Kabupaten Semarang to 0.48. In 2028 there is only one district that can meet the needs of water or surplus water is Banyubiru subdistricts with a carrying capacity value of 1.96. The condition occurs in line with the land cover change that affects water availability, as well as a significant increase in population, causing water needs to increase as well. The results of this research can be input for the Semarang Regency government in determining the future policy, especially in the development.